Situation Report: Poland, 21 February 1983 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The 1982 Plan Fulfillment: Is the Economic Reform Working? Stocktaking in the Party / by Anna Swidlicka Final Version of PUWP Ideological Declaration Expected at Plenum Poor Results in the Economic Reform Test Cracow's [Kraków's] Party Intelligentsia Club Dissolved "Solidarity Today": The Underground Issues a New Action Program Radio Solidarity Organizers Convicted / by Jan de Weydenthal Two Poles in Budapest / by Anna Swidlicka